Desenvolvimento do conceito de uma prótese transtibial de tornozelo e pé com articulações elásticas - Supptitz, Volmir (2025)
Due to accidents, natural deformations and congenital sequelae, there is a growing need for replacing human body`s limbs. Prostheses are components used to replace a lost or malformed limb. Conventional ankle and foot prostheses absorb, in the cushioning of human gait, only the movements of dorsiflexion and plantar flexion. This work aims at developing the concept of a transtibial ankle and foot prosthesis with increased movement freedom through elastic joints. Transtibial prostheses with elastic joints are an important innovation in the field of prosthesis technology. These elastic joints are designed in order to simulate the natural movement of the foot and the ankle, providing users with a more fluid and comfortable gait. The methodology will be used to develop this product, and it will consist of the following steps: literature review, process methods for planning, making a complete list of requirements and analysis of the provisions on the product and functionality and design of the product. The study was developed through stages of the designing methodologies found in the literature, and so, two phases of a designing methodology were applied sequentially: design specification and conceptual design, used systematically to enable the continuation of future work and the application of its concept in device manufacture. The areas of biomechanics, human gait, types of prostheses, elastic materials (polymers), rigid materials (carbon fiber) were considered to obtain the design of a concept for a low-cost, safe prosthesis with ankle and foot movements similar to those of the human body. The rigid materials aim at providing greater resistance to the device basic elements and the elastic materials to ensure the movements of the ankle and foot joints. This study presented the development of a device concept designed with a focus on the user and the interaction that the user will have with the product.